Conjunctival Metaplasia after Pterygium Excision and Limbal Autograft. Issue 3 (March 2015) - Han, Sang Beom; Yang, Hee Kyung; Hyon, Joon Young; Wee, Won Ryang
ABSTRACT: Purpose: To investigate the changes of conjunctival epithelium in the pterygium and donor graft sites after pterygium excision and limbal conjunctival autograft. Methods: This study included 16 eyes of 15 patients who underwent pterygium excision and limbal conjunctival autograft. Epithelial impression cytology specimens of both the pterygium and donor graft were obtained preoperatively and at months 1, 3, and 6, at the pterygium and donor graft sites, respectively. In each specimen, changes in the conjunctival epithelium, including the nucleus-to-cytoplasm (N/C) ratio and goblet cell density (GCD), were evaluated. Morphologic changes in the cells and nuclei were also evaluated. Results: Preoperatively, both N/C ratio and GCD were significantly higher in specimens from the pterygium than in those from the donor site. At both sites, GCD decreased rapidly at 1 month after surgery and then gradually recovered. No significant difference in GCD was found between the two sites at 1, 3, and 6 months postoperatively. Although there was no significant difference in the N/C ratio at 1 and 3 months, the N/C ratio at the pterygium site was significantly greater than that at the donor site at 6 months. At 6 months postoperatively, changes suggesting squamous metaplasia, including elongation of the cells and pyknotic changes in the nuclei, were noted in five samples (31.3%) from the pterygium site but not in any of the samples obtained from the donor site. Conclusions: Conjunctival epithelial metaplasia may return after pterygium removal, which may be associated with the high rate of pterygium recurrence.